Stakeholders' perceptions of the cluster system in a secondary school in Rundu, Namibia - Topnaar, P E (Rhodes University, Faculty of Education, Department of Education, 2006)
Since independence in 1990, various efforts have been made to improve the quality and management of Namibian schools, including the Basic Education Project (BEP-Project). In collaboration with the Geselschaft fur Technische Zusammenarbeit (GTZ), the BEP-Project has supported the implementation of important Government programs, such as Lower Primary reform and the cluster system. In 1995 the BEP-Project began to address educational needs in the Rundu education region. It was believed that Rundu had in the past been the most neglected region, especially with regard to education. The school cluster system was devised to facilitate new ways of education service delivery and to address the question of improving education standards. The purpose of this research is to answer the question: "How do the management and staff of a secondary school in the Rundu region of education experience a school cluster system?" To this end, the research seeks to determine what potential the cluster system holds and how that may be realised, and to also establish whether there is any evidence of change in management practices. A case study method has been employed to gain insight into the cluster system as a management tool. Ten respondents, all of whom have been employed at the school in question for a considerable period of time, were interviewed before and after the implementation of the cluster system. The research disclosed that disparities and tension in the school were legacies of the colonial education system, but that the cluster system had bridged the gap and enhanced uniformity and cooperation. Sharing of ideas on educational issues and constant interaction created a conducive environment for academic performance. The case study further disclosed that parental involvement in decision making is still a course for concern and that the cluster system has not yet addressed this issue. The study has shown that decentralisation has taken place and that rural schools are no longer operating in isolation. A lack of innovative ideas has hampered training as a cluster activity. From the research, it is evident that schools have previously operated on an individual basis, but that the cluster system has created the opportunity for schools to interact on a regular basis. This study is timely and of national importance. I anticipate that this study will be of use to policy makers in making decisions for the future development of the cluster system.
Keywords: School management and organization -- Namibia -- Rundu; Education -- Namibia -- Rundu; Educational leadership -- Namibia -- Rundu; Educational change -- Namibia -- Rundu